Wild deer as a source of infection for livestock and humans in the UK - Böhm, Monika; White, Piran C.L.; Chambers, Julia; Smith, Lesley; Hutchings, M.R. (The veterinary journal (1997), 2007)
Wild deer can feature in the epidemiology of a wide range of livestock and human diseases in the United Kingdom by representing a source of disease via various transmission routes. This review highlights current and possible future infections of deer in the UK which may have an impact on livestock and/or human health. Increases in deer abundance as well as range expansion are likely to exacerbate the potential for disease persistence due to the formation of multi-species deer assemblages, which may act as disease reservoirs. Climatic changes are likely to have a direct impact on the presence and abundance of various pathogens and their vectors, so that with a warming climate exotic diseases may play a role in future UK livestock and wildlife disease management. This paper highlights the need for a monitoring strategy for wildlife diseases, in particular infections in wild deer, in the UK.